2018
DOI: 10.1002/jmr.2752
|View full text |Cite
|
Sign up to set email alerts
|

AFM‐based nanomechanical characterization of bronchoscopic samples in asthma patients

Abstract: Asthma is not a single disease, but recently, it is considered as a syndrome characterized through various clinical presentations and different etiopathologies. Large degree of the disease heterogeneity manifests in distinct characteristics that translate into variability of properties at single cell and molecular levels. Here, we conducted measurements of mechanical properties of bronchial tissue samples collected from patients suffering from asthma. The results obtained from different applied protocols for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…It is also fascinating that AFM studies have also reported close correlation between inflammatory diseases, such as asthma, and the mechanical softening of tissues [47,50]. The mechanosensitive production of insulin from islets was confirmed by AFM-based nano-indentation experiments performed on transgenic DORmO mouse model of type 1 diabetes [50].…”
Section: Mechanical Compliancementioning
confidence: 82%
See 3 more Smart Citations
“…It is also fascinating that AFM studies have also reported close correlation between inflammatory diseases, such as asthma, and the mechanical softening of tissues [47,50]. The mechanosensitive production of insulin from islets was confirmed by AFM-based nano-indentation experiments performed on transgenic DORmO mouse model of type 1 diabetes [50].…”
Section: Mechanical Compliancementioning
confidence: 82%
“…For example, erythrocyte cells were isolated from blood samples in order to investigate hereditary spherocytosis, iron deficiency anemia, sickle cell disease, and type 2 diabetes using AFM [27,[42][43][44][45][46]. In addition, it is relatively easy to obtain tissue samples from asthma patients for AFM studies because bronchial tissues can be collected through routine bronchoscopy [47]. However, studies on some diseases require more painful procedures for specimen collection.…”
Section: Ivyspringmentioning
confidence: 99%
See 2 more Smart Citations
“…A virtual issue appeared in the Journal of Molecular Recognition and is linked with this editorial. Ten research articles composed this special issue Pleskova S. N., Gorshkova E. N., and Kriukov R. N. Dynamics of formation and morphological features of neutrophil extracellular traps formed under the influence of opsonized Staphylococcus aureus .…”
Section: Afmbiomed Conferencesmentioning
confidence: 99%